Atividade antimicrobiana da carbodiimida (EDC) sobre microorganismos presentes em lesões cariosas - Estrêla, Renata Pereira [UNESP] (Universidade Estadual Paulista (Unesp), 2014)
It has been demonstrated that carbodiimide (EDC) is a potent protease inhibitor (MMPs) and is able to improve the mechanical properties of collagen when applied on the demineralized dentin. However, there is no information about its antimicrobial effect on microorganisms commonly found in caries lesions or even after its removal. Objective: To investigate the antimicrobial activity of different concentrations of EDC against microorganisms present in caries lesions. Methods: EDC solutions were prepared and tested against S. mutans and sobrinus, L. acidophilus and Candida albicans. Initially, the agar diffusion test was used, where paper discs were impregnated with 2, 1, 0.5, 0.3 or 0.1 mol/L EDC, 0.12% chlorhexidine, nistatin 1% or Sorensen’s buffer pH 6.2 (control) (n=6). Then, the minimum inhibitory (MIC) and bactericide concentrations (MBC) of EDC were determined against L. acidophilus using turbidity. Finally, the growth inhibitory activity of EDC (from 0.01 to 2 mol/L) against L. acidophilus in monoespecies biofilm was defined using the XTT assay (n=6). Data were submitted to ANOVA and Tukey tests or Mann-Whitney (p<0.05). Results: For the agar diffusion test, lack of antimicrobial activity was seen for EDC at 0.1 and 0.3 mol/L, as well as for the control group. 0.5, 1 and 2 mol/L EDC exerted a growth inhibitory effect only against L. acidophilus. The MIC for EDC was set as 0.01 mol/L and the MBC as 0.03 mol/L. Concentrations equal to or greater than 0.05 mol/L were capable of significantly reducing the metabolism of L. acidophilus when in monospecies biofilm. This reduction ranged from 84.2% for 0.05 mol/L to 93.4% for 2 mol/L. Conclusion: EDC exerted antibacterial activity only against L. acidophilus significantly reducing its growth in planktonic suspension and its metabolism in biofilms in the concentration of 0.05 mol/L or higher.

Tem sido demonstrado que a carbodiimida (EDC) apresenta notável potencial inibidor de proteases (MMPs) e de melhorar as propriedades mecânicas do colágeno quando aplicada sobre a dentina desmineralizada. Entretanto, não existem informações a respeito de sua ação antimicrobiana sobre microrganismos comumente encontrados em lesões de cárie ou mesmo após a sua remoção. Objetivo: Investigar a atividade antimicrobiana do EDC em diferentes concentrações sobre microrganismos presentes em cavidades cariosas. Métodos: Soluções de EDC foram preparadas e testadas contra S. mutans e sobrinus, L. acidophilus e Candida albicans. Inicialmente, foi utilizado o teste de difusão em ágar, no qual discos de papel filtro foram impregnados com EDC 2, 1, 0,5, 0,3 ou 0,1 mol/L, clorexidina 0,12%, nistatina 1% ou tampão Sorensen pH 6,2 (n=6). Em seguida, foi determinada a concentração inibitória mínima (CIM) e bactericida mínima (CBM) do EDC sobre L. acidophilus em suspensão planctônica (n=9), por meio de turvamento. Por fim, a atividade do EDC (de 0,01 à 2 mol/L) sobre L. acidophilus em biofilme monoespécie foi definida por meio do ensaio de XTT (n=6). Os dados foram submetidos aos testes estatísticos de ANOVA e Tukey ou Mann-Whitney (p<0,05). Resultados: No teste de difusão em ágar, nenhuma atividade antimicrobiana foi observada para EDC nas concentrações de 0,1 e 0,3 mol/L, assim como para o grupo controle. EDC 0,5, 1 e 2 mol/L exerceu efeito antimicrobiano apenas sobre L. acidophilus. A CIM do EDC foi de 0,01 mol/L e a CBM foi de 0,03 mol/L. Todas as concentrações de EDC igual ou superiores a 0,05 mol/L foram capazes de reduzir significantemente o metabolismo do biofilme formado por L. acidophilus. Essa redução variou de 84,2 para 0,05 mol/L até 93,4% para 2 mol/L. Conclusão: O EDC apresentou atividade antimicrobiana apenas contra L. acidophilus reduzindo significantemente o crescimento deste microrganismo quando em suspensão...
Keywords: Agentes antibacterianos; Lactobacillus acidophilus; Odontopediatria